Minimization of passive components in multi-level flying capacitor DC-DC converter - Ponniran, Asmarashid (The Institute of Electrical Engineers of Japan, 2016)
In this paper, we propose a minimization design method of the inductance and the capacitance of the flying capacitors for a multi-level flying capacitor DC-DC boost converter (FCBC). The effectiveness of the small capacitances of the flying capacitors in three-level and five-level FCBCs is investigated. We experimentally confirmed that the distortion of the voltage across the input source and the input inductor is drastically reduced by increasing the number of levels. Thus, a small inductance value and a small capacitance value can be used for the input inductor and the flying capacitors, respectively, in an n-level FCBC. Therefore, the minimization of passive components in multi-level FCBCs is achieved. Moreover, the achieved maximum efficiencies of the designed three-level and five-level FCBCs are 98.5% and 97.8%, repectively, at an output power of 1 kW.